New Delhi mass transport system Metro certified to EMS-ISO 14001 at construction stage - Madari, Ushakiran (Knovel, 2010)
Delhi Metro Rail Corporation's plans to cover the New Delhi area with a metro rail network by 2021 are the first metro system to be awarded ISO 14001 certification during the construction phase for their implementation of an Environmental Management System (EMS).
Keywords: Delhi Metro Rail Corporation Ltd.; Local transit -- India -- New Delhi.; Environmental management -- India -- New Delhi.; India -- New Delhi.; elektronické knihy; electronic books